Ebü’l-Berekât en-Nesefî’nin Medârikü’t-tenzîl’inde Sahâbe Tefsiri - (:unkn) unknown (Fatih Sultan Mehmet Vakıf Üniversitesi, Lisansüstü Eğitim Enstitüsü, 2022)
Temel İslâm ilimlerinin hemen hemen her dalında pek çok muteber eser veren Ebü’l-Berekât Nesefî’nin tefsir sahasında kaleme aldığı Medârikü’t-tenzîl ve hakâiku’t-te’vîl adlı eseri, yazıldığı dönemden günümüze kadar önemini korumuş ve her asırda kaynak eser olarak telakki edilmiştir. Söz konusu eserin sahâbe tefsiri bağlamında ele alındığı bu çalışma, girişten sonra üç bölümden oluşmaktadır. Birinci Bölüm’de; Nesefî’nin hayatı, eserleri, Medârikü’t-tenzîl adlı eserinin tanıtımı ve ana hatlarıyla sahâbe tefsiri üzerinde durulmuş; İkinci Bölüm’de, Nesefî’nin tefsirinde rivayetlerine yer verdiği, Hz. Peygamber’e (s.a.v.) yakınlıkları ve ilmî yetkinlikleriyle sahâbe arasında öne çıkan bazı sahâbîlerin tefsir rivayetlerine örnekler verilmiş; Üçüncü Bölüm’de, Medârikü’t-tenzîl’de yer alan rivayetler, evvelâ itikâdî, fıkhî, ahlâkî, peygamber kıssaları ve fezâilü’l-Kur’ân şeklindeki başlıklarla konu, ardından Kur’ân’ın Kur’ân’la tefsiri, kavlî veya fiilî Sünnet’le tefsiri, nesih olgusu, kıraat, tahsîs, dilbilimsel metot ve ictihâdla tefsiri gibi başlıklarla yöntem açısından incelenmiştir. Sonuç’ta, Medârikü’t-tenzîl’de en çok rivayeti bulunan sahâbîler, rivayetlerinin konu dağılımı ve Nesefî’nin rivayeti zikretme metodu gibi eserden çıkarılan hususlar belirtilmiştir.

Abu al-Berekat Nesefi's Medariku't-tenzil and hakaiku't-te'vil, which he wrote in the field of tafsir, who gave many reliable works in almost every branch of basic Islamic sciences, has maintained its importance from the time it was written to the present day and has been published as a source work in every century this work, which is considered in the context of the commentary of the companions, consists of three parts after the introduction. In the First Part; Nesefi's life, works, the introduction and outline of his work Medariku't-tenzil are discussed on the commentary of the companions; In the Second part, Nesefi's tafsir narrations of some Companions, who were prominent among the Companions with their closeness and their scientific competence to the Prophet (pbuh) are given. In the Third Part; the narrations contained in the Medariku't-tenzil, first of all the topic with titles such as itikadi, fiqh, moral, past ummah and prophet's stories and the virtue of the Qur'an, and then then the interpretation of the Qur'an with the Qur'an, interpretation with the verbal or actual Sunnah, abrogation fact, Qur’an’s multiple readings, designation, linguistic method and the interpretation of matters of individual reasoning been studied. In the Conclusion of our study, the results obtained from the work such as the companions who have the most narrations in Medarikü't-tenzil, and the subject distribution of their narrations and the method of mentioning the narration of Nesefi are stated.
The Commentary of the Companions in Abu Al-Berekat Nesefi's Medariku’t-Tenzil
Keywords: Medârikü’t-tenzîl; Ebü’l-Berekât Nesefî; Sahâbe; Sahâbe Tefsiri; Abu al-Berekat Nesefi; Companions; Commentary of the Companions; Commentary